Auditory-visual mental/ emotional conditioning method for youth boxing sport - Khaervarina, A. F.; Matveyeva, L. M.; Yamileva, R. M.; Shayakhmetova, E. Sh.; Ogurechnikov, D. G. (Theory and Practice of Physical Culture, 2019)
Youth boxing sport systems are designed to develop a wide variety of neurodynamic, energy control, mental and physical qualities controlled by the relevant central nervous system mechanisms. Objective of the study was to provide a psychophysical basis and test benefits of a new auditory-visual mental/ emotional conditioning method in application to junior boxers. The study was run at the Bashkir State University sport center in the special precompetitive training period, with the 13-14 boxers (n=72) sampled for the study. The boxers` mental control progress was tested every two days by Psycho-physiologist Test System on the C. Spielberger State-Trait Anxiety inventory and V.A. Doskin Well-being, Activity, Mood (WAM) scale. The method was tested beneficial as verified by the EG versus RG significant progress in the state anxiety, wellbeing, activity and mood test rates. The auditory-visual mental/emotional conditioning method was found to significantly improve the mental and physical tolerance to stressors, mitigate excessive tensions, increase tolerance to mental fatigue, and improve the working capacity and mood. The auditory-visual mental/ emotional conditioning method was tested on the central nervous system-type-specific basis to find that the individuals with the weak and strong central nervous system types need 6-8 and 10 mental/ emotional conditioning sessions for progress, respectively.